From the cross to divinity: the transformation of Jesus in Greco-Roman Antiquity - Magalhães Coelho, André (Romanitas - Revista de Estudos Grecolatinos, 2026)
This article explores the metamorphosis of Jesus, from a humble Jewish preacher who was crucified, to being elevated to divinity by Christians in ancient Greece and Rome. After his death, his disciples began to worship him as God. This raises questions about how a crucified peasant managed to achieve the status of Lord of the universe. The method we will employ for this research will be bibliographical.